2023
DOI: 10.1002/lsm.23681
|View full text |Cite
|
Sign up to set email alerts
|

Nonablative monopolar radiofrequency for the reduction of facial pores and sebum excretion in Thai patients: A novel approach

Thanya Techapichetvanich,
Woraphong Manuskiatti,
Supisara Wongdama
et al.

Abstract: Background: Enlarged facial pores are visible topographic features of the skin that have been associated with cutaneous photoaging and increased sebum production. It has remained a common dermatologic concern, gaining a significant number of in-clinic consults. Available treatment modalities often operate on a single mode of action, consequently offering limited and short-term outcomes.Objective: This study aimed to evaluate the long-term efficacy and safety of a nonablative monopolar radiofrequency (NMRF) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This reduction began 1 month after the initial treatment, demonstrating a noteworthy 41% decrease from the baseline at the 6‐month mark following the second treatment. These improvements in pore size align with the findings by Techapichetvanich et al, who utilized NMRF to improve pore size in Thai patients 13 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This reduction began 1 month after the initial treatment, demonstrating a noteworthy 41% decrease from the baseline at the 6‐month mark following the second treatment. These improvements in pore size align with the findings by Techapichetvanich et al, who utilized NMRF to improve pore size in Thai patients 13 …”
Section: Discussionsupporting
confidence: 88%
“…These benefits include the reduction of inflammatory AV lesions and decreased skin oiliness. The noted observations were substantiated in a study done by Techapichetvanich et al, 13 where NMRF treatments were found to reduce sebum excretion and the perception of skin oiliness. These results were linked to the mechanism of action of NMRF involving volumetric heating of the sebaceous glands and subsequent suppression of sebum excretion.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The main differences between that study and our previous study were the number of treatment sessions and the characteristics of the participants. Our previous study included 10 women and 9 men with an average pore diameter of >0.3 mm on the cheeks, and the patients underwent two monopolar RF treatment sessions at a 4-week interval [26]. A single monopolar RF treatment did not have a pore-reducing effect in patients with general aging compared with patients who had large pores.…”
Section: Discussionmentioning
confidence: 99%